Development of Aptamer-Based Point-of-Care Diagnostic Devices for Malaria Using Three-Dimensional Printing Rapid Prototyping - Dirkzwager, Roderick M; Liang, Shaolin; Tanner, Julian A (ACS sensors, 2016)
We present the adaption of an aptamer-tethered enzyme capture (APTEC) assay into point-of-care device prototypes with potential for malaria diagnosis. The assay functions by capturing the malaria biomarker Plasmodium falciparum lactate dehydrogenase (PfLDH) from samples and using its intrinsic enzymatic activity to generate a visualizable blue color in response to Plasmodium positive samples. Using three-dimensional (3D) printing rapid prototyping, a paper-based syringe test and magnetic bead-based well test were developed. Both were found to successfully detect recombinant PfLDH at ng mL–1 concentrations using low sample volumes (20 μL) and could function using purified or spiked whole blood samples with facile sample preparation. The syringe test was found to be more analytically sensitive but required more additional preparation steps, while the well test required fewer steps and hence may be better suited for future clinical testing. Additionally, the development reagents required for the color response were fully stabilized through desiccation with sugar stabilization agents and could withstand temperatures as high as 90 °C. This study demonstrates how a previously reported biochemical assay can be adapted into workable point-of-care device prototypes by using 3D printing rapid prototyping. This novel technology, intended for rapid diagnostic tests (RDTs) for malaria, is distinct and carries many potential advantages relative to established lateral flow immunochromatographic approaches.